2016
DOI: 10.1002/smll.201603109
|View full text |Cite
|
Sign up to set email alerts
|

One‐Step Microfluidic Synthesis of Nanocomplex with Tunable Rigidity and Acid‐Switchable Surface Charge for Overcoming Drug Resistance

Abstract: Multidrug resistance (MDR), is the key reason accounting for the failure of cancer chemotherapy, remains a dramatic challenge for cancer therapy. In this study, the one-step microfluidic fabrication of a rigid pH-sensitive micellar nanocomplex (RPN) with tunable rigidity and acid-switchable surface charge for overcoming MDR by enhancing cellular uptake and lysosome escape is demonstrated. The RPN is composed of a poly(lactic-co-glycolic acid) (PLGA) core and a pH-sensitive copolymer shell, which is of neutral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 49 publications
0
40
0
Order By: Relevance
“…An exception is that the rate of internalization could be interfered by attaching ligands (HER‐2) to the surface of mesoporous silica nanoparticles. Overall, rigid nanocomplexes prevail the soft counterparts in cellular uptake, endosomal escape, and therapeutic efficiency …”
Section: Key Features Of Nanoparticles Required For Efficient Cancer mentioning
confidence: 99%
“…An exception is that the rate of internalization could be interfered by attaching ligands (HER‐2) to the surface of mesoporous silica nanoparticles. Overall, rigid nanocomplexes prevail the soft counterparts in cellular uptake, endosomal escape, and therapeutic efficiency …”
Section: Key Features Of Nanoparticles Required For Efficient Cancer mentioning
confidence: 99%
“…As novel nanomaterials with diverse surface properties have been developed, surface modification and functionalization with lots of additives and agents are usually adopted, and thus efficient post-processing is highly desired to obtain pure products. Especially with the development of in situ modification or functionalization, reproducible microfluidic purification or separation is necessary to maintain the surface properties of the nanomaterials [27,91]. As a matter of fact, most post-processing strategies require separating modified/functionalized nanoparticles from liquid environment, in which case the nanomaterials tend to agglomerate at the phase interfaces.…”
Section: Surface Modification/functionalization and Purificationmentioning
confidence: 99%
“…Meanwhile, requirements on nanomaterial dimensions, unique surface chemistry, more special sizes (much smaller or larger in one or two dimensions), and highly uniform structures have also become highly demanded. Especially in recent years, novel nanomaterials, such as hybrid quantum dots, composite particles, nanowires, nanorods, and other 2D-/3D-structured nanomaterials, require higher controllability for the preparation processes [26,27]. Correspondingly, multistep operations, complex conditions, and manipulation in multiphase flow systems are typically necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Simulation revealed that the deformability of these soft lipid/PLGA nanostructures was energetically unfavorable for the cellular uptake (Figure C). These rigid P‐L NPs have been applied as nanocarriers to encapsulate therapeutic agents and revealed significantly enhanced cellular uptake and antitumor effects . In another study by Jiang's group, a similar HFF microfluidic device was used to synthesize lipid–polymer assemblies with the same size but covered with either a lipid monolayer or a lipid bilayer.…”
Section: Microfluidics For Fabrication Of Sddss With Well‐controlled mentioning
confidence: 99%
“…This large difference results in heterogeneous self‐assembly conditions of amphiphiles or polyelectrolytes across the reactor . Therefore, bulk‐mixing‐based sDDS fabrication is not easy to precisely control over the sDDS properties: size, rigidity, shape, drug‐loading efficiency, and interbatch reproducibility. This inconsistency in sDDS structure, and thus biological performance, complicates clinical translation.…”
Section: Introductionmentioning
confidence: 99%